Pembayaran Sanksi Adat untuk Penetapan Nasab Anak dalam Perspektif Hukum Islam (Studi Kasus di Nagari Simpang Tonang Kecamatan Dua Koto Kabupaten Pasaman) - Neny Tria Ulvades; Muhammad Ridha (AHKAM, 2026)
The determination of a child’s lineage under customary law and Islamic law has received attention in various studies, but research specifically examining the payment of customary sanctions as a basis for recognizing a child’s lineage in customary communities from the perspective of Islamic law remains limited. This study aimed to analyze the practice of paying customary sanctions in determining a child’s lineage in Nagari Simpang Tonang, Dua Koto Subdistrict, Pasaman Regency, and to examine its status from the perspective of Islamic law. The study employed a qualitative approach with a case study design. Informants were selected through purposive sampling and included ninik mamak, alim ulama, nagari officials, and community members who understood the practice of paying customary sanctions. Data were collected through interviews, observation, and documentation and were subsequently analyzed using qualitative descriptive analysis through data reduction, data display, and conclusion drawing. The findings showed that the payment of customary sanctions functions as a social settlement mechanism to restore family honor, maintain social order, and provide social recognition to children born from pregnancies outside marriage. However, from the perspective of Islamic law, the payment of customary sanctions cannot serve as a basis for determining lineage because lineage can only be established in accordance with the provisions of Sharia. This study confirms that the applicability of customary law in matters of lineage is limited by the principles of Islamic law. These findings strengthen the application of ‘urf theory in analyzing the relationship between customary law and Islamic law and imply the importance of harmonizing customary values with Sharia provisions in resolving family-related issues. The results of this study can serve as a consideration for customary leaders, religious leaders, and the nagari government in formulating policies that continue to address the social interests of the community without contradicting the principles of Islamic law.